Perancangan Sistem Informasi Akademik Sekolah Menengah berbasis Website - Bhagaskoro Putra Nindyalit; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The current academic system in schools still uses the traditional way, which is still using books as a means of recording. The large number of students starting from grade 1 to grade 3 made the school staff in the administration and discipline department experience problems when backing up data. The data still cannot be processed automatically, so students who need academic information must wait for the data to be processed. This raises several problems, one of which is when students want to get academic and administrative information. Students take a long time and have to find the teacher and staff concerned. Teachers have problems making copies of data for backup when books or data are lost or damaged. Based on the problems found, an information system is designed that will facilitate the process of managing student data by teachers and staff and facilitate the provision of academic information for students. The design carried out in this study only displays an interface for the user of the student actor. In testing user interaction and information system interfaces, the sample uses student actors and 6 respondents are obtained. The user interaction trial on the interface that was built was acceptable to the user and resulted in a score of 75% (Agree).